The Fekete–Szegö functional associated with m-th root transformation using conical domains - Gurusamy, P.; Çağlar, M.; Sivasubramanian, S.; Cotirla, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 Let A be the class of analytic functions in the open unit disk U={zC|z|<1}. Let R_α ^p be the operator defined on A by equation*R_α ^p=f(z) * z(1-z)^2(1-α ) .equation* A function f in A is said to be in the class k-SP_α ^p if R_α ^p(f) is a k-parabolic starlike function. We focus on the Fekete–Szegö inequality associated with m-th root transformation using conical domains for this class.